Development of α-Synuclein Real-Time Quaking-Induced Conversion as a Diagnostic Method for α-Synucleinopathies - Nakagaki, Takehiro; Nishida, Noriyuki; Satoh, Katsuya (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease, dementia with Lewy bodies, and multiple system atrophy are characterized by aggregation of abnormal α-synuclein and collectively referred to as α-synucleinopathy. Because these diseases have different prognoses and treatments, it is desirable to diagnose them early and accurately. However, it is difficult to accurately diagnose these diseases by clinical symptoms because symptoms such as muscle rigidity, postural dysreflexia, and dementia sometimes overlap among these diseases. The process of conformational conversion and aggregation of α-synuclein has been thought similar to that of abnormal prion proteins that cause prion diseases. In recent years, in vitro conversion methods, such as real-time quaking-induced conversion, have been developed. This method has succeeded in amplifying and detecting trace amounts of abnormal prion proteins in tissues and central spinal fluid of patients by inducing conversion of recombinant prion proteins via shaking. Additionally, it has been used for antemortem diagnosis of prion diseases. Recently, aggregated α-synuclein has also been amplified and detected in patients by applying this method and many clinical studies have examined diagnosis using tissues or cerebral spinal fluid from patients. In this review, we discuss the utility and problems of α-synuclein real-time quaking-induced conversion for antemortem diagnosis of α-synucleinopathies.